2017
DOI: 10.1186/s13568-017-0439-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventing subclinical necrotic enteritis through Lactobacillus johnsonii BS15 by ameliorating lipid metabolism and intestinal microflora in broiler chickens

Abstract: Increasing studies have focused on the beneficial effects of Lactobacillus johnsonii in certain diseases. Here, we studied the prevention ability of a probiotic strain, L. johnsonii BS15 on subclinical necrotic enteritis (SNE), and its underlying mechanism. 180 male Cobb 500 chicks were randomly allotted into three groups and administrated with BS15 (1 × 106 cfu/g) or Man Rogosa Sharpe liquid medium throughout a 28-day experimental period. With the exception of the normal group, SNE infection was treated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 71 publications
1
45
0
1
Order By: Relevance
“…The correlation between increased IL-17A expression and L. johnsonii abundance parallels the intestinal induction of IL-17A observed in response to tightly adherent symbiotic species (60)(61)(62)(63)(64). L. johnsonii is an established probiotic that has been demonstrated to have beneficial effects when applied in poultry production (48)(49)(50)(51)(52)(53). Several modes of action have been proposed for probiotic strains of L. johnsonii but underlying these is the multi-modal ability of the species to affect epithelial gut cell adherence (65)(66)(67)(68), which we propose will induce the expression of IL-17A.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The correlation between increased IL-17A expression and L. johnsonii abundance parallels the intestinal induction of IL-17A observed in response to tightly adherent symbiotic species (60)(61)(62)(63)(64). L. johnsonii is an established probiotic that has been demonstrated to have beneficial effects when applied in poultry production (48)(49)(50)(51)(52)(53). Several modes of action have been proposed for probiotic strains of L. johnsonii but underlying these is the multi-modal ability of the species to affect epithelial gut cell adherence (65)(66)(67)(68), which we propose will induce the expression of IL-17A.…”
Section: Resultsmentioning
confidence: 70%
“…In broiler chickens, administration of a L. johnsonii isolate has been reported to improve growth performance (48). Subsequently it was reported that meat from L. johnsonii treated birds had higher nutritional value and the birds showed resistance to the development of necrotic enteritis (49,50). Similar results were obtained by administering L. johnsonii LB1 to piglets to improve performance and reduce diarrhea (51).…”
Section: Discussionmentioning
confidence: 75%
“…Lactobacillus johnsonii BS15 prevented subclinical necrotic enteritis by reducing expression of genes expression of acetyl-CoA carboxylase, fatty acid synthase and sterol regulatory element-binding protein-1c. It also enhanced gene expression of peroxisome proliferator-activated receptor α and carnitine palmitoyltransferase-1 while helped in mitigating subclinical necrotic enteritis (Qing et al 2017). Lactobacillus johnsonii BS15 significantly increased in the CD3 + CD4 + T-lymphocyte percentage in peripheral blood of birds affected with SNE.…”
Section: Molecular Mechanisms Explaining the Positive Effects Of Probmentioning
confidence: 98%
“…Lactobacillus johnsonii BS15 ameliorated the lipid metabolism and improved the intestinal microflora of chickens. Thus, Lactobacillus johnsonii BS15 can be used as potential probiotic for prevention of SNE (Qing et al 2017). Lactobacillus johnsonii BS15 improved the blood parameters related to immunity in chickens infected with SNE.…”
Section: Lactic Acid Bacteria As Probiotics For Prevention Against Snementioning
confidence: 99%
See 1 more Smart Citation